1993
DOI: 10.1016/s0886-3350(13)80274-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity in multifocal intraocular lenses

Abstract: Contrast sensitivity was measured in two groups of 20 patients each implanted with refractive and diffractive multifocal intraocular lenses and in two control groups of 20 patients each--the first group implanted with a monofocal IOL and the second phakic subjects. All cases had a postoperative follow-up of at least one year and a corrected visual acuity of 20/20- or better. We used two psychophysical tests, Pelli Robson test chart and Vistech 6500 test chart, and an objective test, visual evoked potentials (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…We used the CAT-2000 for contrast sensitivity testing because with and without glare, it is more sensitive than other contrast sensitivity testing devices. 11,12 Many studies [13][14][15][16][17][18][19][20][21] report that contrast sensitivity is impaired with most multifocal IOLs, especially diffractive IOLs. However, because the multifocal IOL we used has an aspheric optic and a low add power, contrast sensitivity with and without glare under photopic and mesopic conditions was markedly better than with the C4.0 D IOLs we tested in the clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the CAT-2000 for contrast sensitivity testing because with and without glare, it is more sensitive than other contrast sensitivity testing devices. 11,12 Many studies [13][14][15][16][17][18][19][20][21] report that contrast sensitivity is impaired with most multifocal IOLs, especially diffractive IOLs. However, because the multifocal IOL we used has an aspheric optic and a low add power, contrast sensitivity with and without glare under photopic and mesopic conditions was markedly better than with the C4.0 D IOLs we tested in the clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Second, contrast sensitivity tends to be impaired and glare disability greater, in particular with diffractive multifocal IOLs. [13][14][15][16][17][18][19][20][21] Third, halo and glare symptoms are more severe with multifocal IOLs, specifically refractive models. [30][31][32][33] The current study showed that the aspheric diffractive multifocal IOL with low add power improved intermediate visual acuity significantly and provided contrast visual acuity with and without glare similar to that with monofocal IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, alguns estudos envolvendo LIOs multifocais, mostram resultados de SC consideravelmente diferentes (11)(12)(13)(14)(15)(16)(17)(18) ; entretanto deve-se ter cuidado com comparações, devido às diferenças entre pacientes, tabelas, condições de iluminação e examinadores.…”
Section: Discussionunclassified
“…The list of IOCL complications is long and also includes some less than sight threatening events such as pupillary distortion and/or retraction (Waring, 1998), poor IOCL ®xation with consequent reopening of the globe (Menezo et al, 1998;Waring, 1998), incorrect lens power (Menezo et al, 1998), and a reduction in contrast sensitivity in multifocal implants (Ravalico et al, 1993).…”
Section: Intraocular Contact Lenses ð Medical and Scienti®c Consideramentioning
confidence: 99%